The History and Relevance of the Beneficial Ownership Concept in Tax Treaties ? Specifically in the context of the Introduction of the Principal Purpose Test - Ross, Shannen-Leigh (Department of Finance and Tax, 2024)
The term Beneficial Ownership was primarily introduced to prevent treaty shopping and to ensure that only those liable to tax could claim treaty advantages. However, the term is not explicitly defined in the Organisation for European Economic Co-operation Model Tax Convention on Income and on Capital (OECD MTC), leading to its subjective interpretation and asymmetrical application, which may provide opportunities for the exploitation of tax treaties. The Principal Purpose Test (PPT) has been introduced as another anti-treaty-shopping provision for tax treaties. The aim of this research was to explore the term Beneficial Ownership to determine whether it is still relevant given the PPT. The research methodology used an interpretative approach, which entailed a systematic exploration of the literature and legal texts. Information from academic literature, double tax agreements, domestic legislation, OECD MTC (reports, commentaries, and materials) and international case laws were collected. Thereafter, a qualitative analysis was conducted to gain a clearer and more comprehensive understanding of the Beneficial Ownership concept and the PPT. The results of this study demonstrated that although the Beneficial Ownership concept is widely used in tax treaties across states, its subjective interpretation, has led to significant risks for double taxation or double non-taxation. In conclusion, the thesis suggests that the PPT is a viable alternative approach to address treaty shopping, although in its current state, the ambiguity of the terms used within the provision raises a few challenges and concerns. However, with the necessary adjustments made to the provision, the PPT has the potential to provide states with a more potent tool to treaty shopping, especially in structured transactions.